When Does an Incidental Chiari I Malformation Require Surgery? A 10-Year Prospective Study on the Evolution and Natural History. (1st September 2019) - Alexander, Hepzibha; Tsering, Deki; Myseros, John S; Magge, Suresh N; Oluigbo, Chima; Sanchez, Carlos E; Keating, Robert F
Abstract: INTRODUCTION: The optimal management of incidental CM-I remains elusive, in part, due to a lack of understanding of its natural history. Despite recent efforts, most studies are limited by their retrospective design, small sample size, and variable follow-up as well as indication for surgery. We present a large-scale, long-term, prospective study of the natural history of incidental CM-I in pediatric patients. METHODS: A single-institution, prospective review of patients with incidental CM-I was performed from 2008 to 2018. CM-I was defined as "incidental" when it was discovered during workup for an unrelated indication in an otherwise asymptomatic individual. Patients were stratified into observation only, early surgery (<6 mo from initial diagnosis) or delayed surgery (>6 mo) groups. To observe the evolution of CM-I, a minimum follow-up of 1-yr was set as the inclusion criteria for patients in the observation only cohort. Demographics, radiographic features, clinical presentation and indications for surgery were analyzed to define parameters for conservative management and determine predictors of surgery. RESULTS: From 777 CM-I patients, 433 (55.73%) were diagnosed incidentally. A total of 390 (90.1%)were managed conservatively while 43 (9.93%) eventually required surgery at an average duration of 10.6 m from diagnosis.Among the surgical cohort, there was a trend toward early surgery with 90.7% undergoing surgery within 3 yr of initial diagnosis (see Kaplan-Meier analysis). Most patients (76%) in the early surgery group presented with a syrinx at initial presentation compared to only 2 (15%) in the delayed surgery group. The remaining patients manifested progressive symptoms.Predictive factors significantly associated with surgery included syrinx, cervicomedullary kinking and gait abnormality ( P < .05). CONCLUSION: Incidental CM-I has a relatively benign natural history and can be managed in a conservative fashion in majority of pediatric patients. However, careful and longterm follow-up, particularly during the first 3 yr after diagnosis is critical since 9.9% of patients are likely to experience a change in clinical or radiographic status necessitating surgical intervention.